COMPARATIVE ANALYSIS OF FINANCIAL TERMS IN ENGLISH AND UZBEK LANGUAGES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Financial terms are an integral part of economic activity. They play an important role in representing finance, banking, investment and other economic processes. English is the main language in global finance, and many terms are being transferred from English to Uzbek. New terms are emerging in modern finance. In English, terms such as "digital banking" (digital bank) and "e-wallet" (electronic wallet) are common. In Uzbek, these terms are translated as "digital bank" and "electronic wallet". This process contributes to the development of the Uzbek language and the formation of specific terminology in the field of banking and finance. Financial terms also depend on cultural and social context. The development of the financial system and economic changes in Uzbekistan affect the change of terms. For example, new economic policies and programs may lead to the introduction of new terms. In English, news and innovations in the field of finance cause changes in terms. Financial terms also affect the education system. Institutions providing education in the Uzbek language in the field of finance and banking are introducing new terms into their programs. This is important for students and professionals in acquiring new knowledge. And in English, financial education is based on many international standards, which ensures global acceptance of terms.